Cognitive behavioral counseling guidelines with web-based cognitive restructuring techniques to overcome anxiety for adolescent experiencing victims of violence - Ni Made Rita Anggreni; Kadek Suranata; Kadek Ari Dwi Arwati (Konselor, 2021)
The objective of this research includes developing, validating a guidebook, and determining the effectiveness of behavioral counseling guidelines using web-based cognitive restructuring techniques/methods to treat anxiety in adolescent victims of violence. The counseling guide is described as a resource for an educator in a school. In relation to the steps for implementing counseling guidance services that are aligned with 4D development model by Thiagarajan (1974). The validity of this guide was evaluated by four experts in the field of counseling and one expert in the field of educational technology. The instrument used contains 14 statements concerning the acceptability of a guide. Validity analysis used calculation formulation of the Content Validity Ratio (CVR) by Lawshe (1975). According to the findings, content validity (CVI) was worth one, indicating that it had a good or unique meaning. This statement states that the behavioral counseling guide developed using cognitive restructuring techniques on a website basis has met the eligibility requirements. The effectiveness test included 30 students who had experienced anxiety as a result of violence, and the research used a one-group pre-test and post-test design method. This effectiveness test was carried out using the t test, the results of the t-test were obtained by ????count = 13.352 and ????????????ble = 2,048 which means that the value of ????count  > ????????????ble , this result indicated that the development of cognitive behavioral counseling guidelines with cognitive restructuring techniques is effective to overcome anxiety in adolescent victims of violence